1997
DOI: 10.2172/479074
|View full text |Cite
|
Sign up to set email alerts
|

Oregon inlet: Hydrodynamics, volumetric flux and implications for larval fish transport

Abstract: The temporal response of Oregon Inlet currents to atmospheric forcing and sea level fluctuations is analyzed using time and frequency domain analysis. Correlations are examined between the atmospheric wind field, the main axial slope of the inlet's water level, inlet flow and T, S properties. Synoptic scale atmospheric wind events are found to dramatically and directly affect the transport of water towards (away from) the inlet on the ocean side, in concert with the contemporaneous transport away from (towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 9 publications
3
11
0
Order By: Relevance
“…The other prominent feature in water level differences is the vast majority of negative values of 30 h low‐pass‐filtered (to remove tide effects) water level differences between the ocean and bay (red curve in Figure b). This indicates a net mean flow directed from the bay toward the ocean which is consistent with previous observations done in one channel of Oregon Inlet located 10 km North of the breach [ Nichols and Pietrafesa , ]. The variation of the water level difference between the ocean and bay as a function of winds becomes more evident using the low‐pass‐filtered water levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other prominent feature in water level differences is the vast majority of negative values of 30 h low‐pass‐filtered (to remove tide effects) water level differences between the ocean and bay (red curve in Figure b). This indicates a net mean flow directed from the bay toward the ocean which is consistent with previous observations done in one channel of Oregon Inlet located 10 km North of the breach [ Nichols and Pietrafesa , ]. The variation of the water level difference between the ocean and bay as a function of winds becomes more evident using the low‐pass‐filtered water levels.…”
Section: Resultsmentioning
confidence: 99%
“…breach [Nichols and Pietrafesa, 1997]. The variation of the water level difference between the ocean and bay as a function of winds becomes more evident using the low-pass-filtered water levels.…”
Section: 1002/2016jc012029mentioning
confidence: 99%
“…The orientation of the Newport River and Beaufort Inlet is southward‐facing, and winds blowing towards the south or southwest would force water out of the Newport River estuary, possibly inhibiting megalopal ingress into there. However, a more likely explanation is that the Newport River is a strongly tidal system, whereas the tidal signal near Oregon Inlet is greatly diminished within 2.5 km of the inlet, and hydrodynamics near Oregon and Hatteras Inlets are much more responsive to regional‐scale wind forcing than tidal forcing (Nichols and Pietrafesa, 1997; Forward et al. , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In Figure 2a,e, we see that when the winds blew from the north and northeast, on the western or shoreward side of Dennis' eye, water levels rose within several hours on the open ocean side of the coast at the Duck, NC. The water level (tide gage) data has been low-pass filtered using a 40-hour half power point Lanczos-Cosine filter [14]. Within the sound system, water levels fell in the northeastern end or upper Pamlico Sound, and rose in the upper Tar-Pamlico River, all within three hours.…”
Section: Analysesmentioning
confidence: 99%
“…The Nichols and Pietrafesa [14] study showed that for periods in excess of a day, the axial flow through Oregon Inlet and sea level slope, are tightly coupled in a 43 cm/sec/meter relationship. Using this stable transform function, we can compute the volumetric flux of water through the inlet.…”
Section: Water Transport Through the Inletsmentioning
confidence: 99%